A study of the symptoms of gastro oesophageal reflux disease and the associated risk factors in a tertiary care centre - Manickam, Santni; Sethuraman, Ganesh; Kuppusamy, Jayachandran (International Journal of Research in Medical Sciences, 2019)
Background: Gastro esophageal reflux disease is the commonest pathologies encountered by gastroenterologist in day to day practice. Longstanding and untreated gastro esophageal reflux disease can lead to many complications including adenocarcinoma. This study was conducted to evaluate the various symptoms and to analyze the lifestyle and dietary factors influencing gastro esophageal reflux disease which can be modified. Methods: Hundred patients with gastro-esophageal reflux disease of age more than 18 years were enrolled in the study. Various patient details including demographic details, lifestyle information and symptomatology data were analyzed and compared with complications. Results: Mean age of gastro esophageal reflux disease patients was 56.09±15.93 years. Gastro esophageal reflux disease is more prevalent in males than females. Gastro esophageal reflux disease is more frequent in BMI <25, greater number of co morbidities and in non-vegetarians. Mean age of gastro esophageal reflux disease with complications was 67±11.53 years and without complications was 52.64±15.57 years. No strong association of smoking, alcohol, spicy foods, fried foods, citrus fruits, heavy meals, tea/coffee, aerated drinks, sleep disturbance and effect on work was identified in gastro esophageal reflux disease. Conclusions: Classical symptoms of gastro esophageal reflux disease were not present in all the patients. Higher age of the patient infers higher risk of complications. Daily episodes of heartburn, regurgitation and retrosternal chest pain implies higher risk of complications. Presence of Helicobacter pylori in gastro esophageal reflux disease patients signify higher risk of complications.